What does the Christian faith offer to new generations? - Oviedo Torró, OFM, Lluís (Razón y fe, 2018)
The transmission of the faith to young people is currently a serious problem. Young people do not need faith or religion and the Church to live and be happy. However, the Christian faith, we believers think, is still valid and topical. In addition to the many benefits that faith continues to provide on a human level, its transmission would provide our young people with a strong religious experience of a God who loves, a firm hope in the resurrection and eternal life and, finally, a non-monistic vision of the human being.